Energy Efficiency: Barriers and Solutions towards Environmental Integrity and Well-being Policies - Zucaro, Amalia; Genovese, Andrea; Lega, Massimiliano; Gonella, Francesco (Journal of Environmental Accounting and Management, 2026)
Energy and resource constraints are increasingly becoming a concern for populations, scientists and policy-makers. Implementing multi-faceted policies capable of maintaining or improving the current living standard, ensuring business and job opportunities as well as preserving environmental integrity and natural capital is becoming a priority in international strategies. One of the most demanding challenges for human beings in the near future is the development of energy policies characterized by low environmental impacts, prevention of resource scarcity and the possibility of achieving socio-economic well-being. This Special Issue focuses on recent developments and visions in the field of energy and resource efficiency to promote sustainable environmental policies at different scales of processes, sectors and society.